ANALYTICAL STUDY OF JOB SATISFACTION AMONG BTC AND SPECIAL BTC TRAINED TEACHERS WORKING AT PREPARATORY STAGE - Singh, Gajendra; Gola, Rajkumari (ShodhKosh: Journal of Visual and Performing Arts, 2023)
It Is Only Through Education That Any Person's All-Round Development Takes Place, He Develops The Society And The Country By Becoming A Useful Member Of The Society. Primary Education Is The Foundation Stone For Making A Child Civilized, Cultured, Without Strengthening It, The Desired Society Cannot Be Achieved, Therefore, There Is Always Pressure On The Leaders Of The Society And The Country, How To Organize This Level Of Education So That The Expected Results Can Be Achieved And The Nursery Being Prepared For The Needs Of The Society And The Country Can Be Given The Right Direction So That They Can Become A Capable Member For The Society And The Country And Can Make Their Important Contribution In The Upliftment Of The Country And Human Society. For All This, It Is Necessary That Such Arrangements Should Be Made According To The Changing Times So That They Are Ready To Receive Education, They Receive Education With Entertainment, They Feel Good In Coming To School And Staying There, This Can Happen Only When The Things Prevalent In The Society Are Available In The School So That The Environment There Does Not Seem Different To Them Which Is Boring With Their Lifestyle. Rousseau Says, 'We Cannot Learn Anything From Such A Student Whom We Hate. Children Should Not Only Come To School But Also Stay There Regularly Till School Hours And Happily Absorb The Information Given On Various Subjects In A Better Way. Various Commissions Have Emphasized From Time To Time That The Stay Of Children In School Should Be Increased. Various Efforts Have Been Made For All This. In Order To Make Teaching Interesting And Comprehensible, Emphasis Has Been Laid On The Job Satisfaction Of Teachers In This Area.